Caregiver Empowerment Through Training and Mentoring on Knowledge of Personal Hygiene Management in Older People - I Gede Putu Darma Suyasa; Ni Luh Putu Inca Buntari Agustini; Israfil Israfil; Ni Luh Dwi Indrayani; Jintana Artsanthia; Ni Kadek Sutini; Ni Wayan Riska Sagita (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2026)
One key aspect of elderly care is personal hygiene management, which directly influences older adults' physical health, psychological well-being, and dignity. Our observation indicates that 6% of older people experience difficulties in maintaining personal hygiene independently. These older people depend on caregivers to maintain their hygiene. However, many caregivers lack adequate knowledge and skills, highlighting the need for practical training and mentoring interventions. This community service activity aimed to enhance knowledge related to personal hygiene management in elderly care by conducting a structured training and mentoring program for caregivers. This activity, carried out in March 2025, included interactive training sessions and one-on-one mentoring involving 41 caregivers from Pedungan and Melinggih villages. Both villages were chosen because our previous studies were carried out in these places. They were representatives of rural and urban areas. To measure the impact of our program, we conducted a pre-post test experimental design without control groups. Knowledge was measured with a self-developed, validated questionnaire. A Wilcoxon Signed Rank Test revealed a statistically significant increase in the knowledge after training, z = -3.829, P < 0.001, with a large effect size (r = 0.6). The median score on the knowledge increased from pre-program (Md = 13) to post-program (Md = 14). Training and mentoring empower caregivers by enhancing their knowledge to better manage the personal hygiene of older people. This approach not only improves the quality of care provided but also contributes to the dignity, comfort, and overall health outcomes of the elderly population. Future programs need to be expanded to include a broader range of caregivers from different areas.